Genomic imprinting and its regulation - Ferguson-Smith, Anne (Henry Stewart Talks, 2007)
Introduction to imprinting, classic embryological and genetic studies, identification and function of imprinted genes, imprinted domains and the organisation of imprinted clusters, epigenetic modifications and genome programming, cis-acting control at imprinted domains, DNA methylation and non-coding RNA, histone modifications, clinical implications
Archived at 2018/05/31